Memories of the Caribbean and America Public Health Symposium - Reinaldo Reyes Mediaceja; Elia Elsa Campañá Cobas; Emma Aurora Bastart Ortiz; Mirtha Romelia Reyes Mediaceja (Centro Provincial de Información de Ciencias Médicas, 2019)
The Caribbean and America Public Health Symposium presented 3 editions (2017, 2018 and 2019) and was sponsored by the Cuban Society of Public Health, the Provincial Chapter of Public Health, Health Provincial Management, the University of Medical Sciences, the Provincial Council of Health Scientific Societies, Camilo Torres Restrepo Teaching Polyclinic, as well as the National Association of Economists and Accountants. Along with this event Ethics and Values and Health Economy workshops were developed. In the third edition the Day of residents in Comprehensive General Medicine also took place. Experiences were exchanged that in the mark of the public health projection, have had impact in the economic, social and scientific spheres. Due to its importance and agreement of the present people, the conclusions taken in plenary session were sent to the provincial decision makers to contribute in the improvement of quality in the care giving, teaching and investigative processes.